2005
DOI: 10.1128/aem.71.11.7461-7471.2005
|View full text |Cite
|
Sign up to set email alerts
|

Proof that Burkholderia Strains Form Effective Symbioses with Legumes: a Study of Novel Mimosa -Nodulating Strains from South America

Abstract: Twenty Mimosa-nodulating bacterial strains from Brazil and Venezuela, together with eight reference Mimosa-nodulating rhizobial strains and two other ␤-rhizobial strains, were examined by amplified rRNA gene restriction analysis. They fell into 16 patterns and formed a single cluster together with the known ␤-rhizobia, Burkholderia caribensis, Burkholderia phymatum, and Burkholderia tuberum. The 16S rRNA gene sequences of 15 of the 20 strains were determined, and all were shown to belong to the genus Burkholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
175
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 40 publications
(43 reference statements)
9
175
1
7
Order By: Relevance
“…T was found to be more closely related to Methylobacterium nodulans (Alphaproteobacteria) based on its DNA and amino acid sequences, but its nifH sequence is closer to free-living Burkholderia (Betaproteobacteria) (Figure 3) [6,7,63]. As stated earlier, in contrast to STM678 T , which nodulates papilionoideae, in our complete genome study we found that B. tuberum sv.…”
Section: Discussioncontrasting
confidence: 47%
“…T was found to be more closely related to Methylobacterium nodulans (Alphaproteobacteria) based on its DNA and amino acid sequences, but its nifH sequence is closer to free-living Burkholderia (Betaproteobacteria) (Figure 3) [6,7,63]. As stated earlier, in contrast to STM678 T , which nodulates papilionoideae, in our complete genome study we found that B. tuberum sv.…”
Section: Discussioncontrasting
confidence: 47%
“…This species has been isolated from nodules of Mimosa pudica, Mimosa diplotricha and Mimosa pigra (synonym Mimosa pellita) in Taiwan (Chen et al, 2001(Chen et al, , 2003a(Chen et al, , 2005b and from M. pudica in northern and southern India (Verma et al, 2004), and the type strain, LMG 19424 T , has been shown to nodulate M. pudica and M. diplotricha effectively (Chen et al, 2003b). More recently, there has been a greater focus on b-rhizobia in the genus Burkholderia, as these are being isolated from Mimosa and related species with much greater frequency than is C. taiwanensis, particularly in South America and Central America (Barrett & Parker, 2005, 2006Chen et al, 2005a), but also in Taiwan from the invasive legume M. pigra (Chen et al, 2005b). However, with the exception of Burkholderia caribensis TJ182, B. phymatum STM815 T and B. tuberum STM678 T (Vandamme et al, 2002), the taxonomic positions of Burkholderia legume symbionts have not yet been described.…”
mentioning
confidence: 99%
“…1). These sequences were compared with published 16S rRNA gene sequences of other Burkholderia species, as described previously (Chen et al, 2001(Chen et al, , 2005a. The phylogenetic analysis showed that these nine strains form a single cluster (99?5-100?0 % 16S rRNA gene sequence similarity) and belong to the genus Burkholderia within the Betaproteobacteria.…”
mentioning
confidence: 99%
“…Although it was generally accepted that legumes were nodulated exclusively by relatives of Rhizobium in the class Alphaproteobacteria, the so-called 'alpharhizobia', over the last 10 years there have been an increasing number of reports of legumes being nodulated by members of the Betaproteobacteria (the so-called 'betarhizobia') (Gyaneshwar et al, 2011). Cupriavidus taiwanensis LMG19424 and Burkholderia phymatum STM815 were among the first identified nodulating betaproteobacterial strains (Gyaneshwar et al, 2011) and both are highly effective nitrogen-fixing symbionts of Mimosa species (Chen et al, 2003(Chen et al, , 2005Elliott et al, 2007;dos Reis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%